2021
DOI: 10.29103/relativitas.v4i2.5257
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Modul Pembelajaran Terhadap Hasil Belajar Kognitif Siswa

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan modul pembelajaran terhadap hasil belajar kgnitif siswa. Jenis penelitian ini adalah Quasi Eksperimental Design, pupulasi yang diambil adalah kelas X semester genap 2020/2021 SMA Negeri 1 Teupah Selatan. Teknik pengambilan Sampel menggunakan desain non probability sampling. Sampel yang diambil adalah kelas X-MIA 1 sebagai kelas eksperimen yang terdiri dari 22 siswa dan kelas X-MIA 2 sebagai kelas kontrol yang terdiri dari 22 siswa. Instrument pengum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of this finding are supported by previous research with the title "The Effect of Using Learning Modules on Students' Cognitive Learning Outcomes" by Fatmi et al (2021) with the results of the research showing through the data analysis test conducted using the independent t-test with a significant on students' cognitive learning outcomes obtained a significant 2-tailed of 0.000 < 0.05 so that Ho is rejected and Ha is accepted. Based on the test analysis, it can be concluded that there is an effect of using learning modules on students' cognitive learning outcomes.…”
Section: The Influence Of Teaching Modules On the Ipas Learning Outco...supporting
confidence: 80%
“…The results of this finding are supported by previous research with the title "The Effect of Using Learning Modules on Students' Cognitive Learning Outcomes" by Fatmi et al (2021) with the results of the research showing through the data analysis test conducted using the independent t-test with a significant on students' cognitive learning outcomes obtained a significant 2-tailed of 0.000 < 0.05 so that Ho is rejected and Ha is accepted. Based on the test analysis, it can be concluded that there is an effect of using learning modules on students' cognitive learning outcomes.…”
Section: The Influence Of Teaching Modules On the Ipas Learning Outco...supporting
confidence: 80%
“…Modules as suitable learning materials must be packaged comprehensively and systematically, including planned learning activities designed to help students understand specific learning objectives. The use of modules in physics learning has been proven to improve students' scientific literacy skills (Mustakim et al, 2020), cognitive learning outcomes (Fatmi et al, 2021), and critical thinking skills (Wahyuni et al, 2017). Based on observations and interviews with several students, it is known that the teaching materials used in optics courses are still limited to textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, Kosasih (2021) explains that a good module, must attract the interest of the reader provide motivation, contain interesting illustrations and consider linguistic aspects so that they are suitable with the ability of the readers and are able to stimulate the personal activities of the reader. Therefore the use of suitable modules will be able to improve students' cognitive learning outcomes (Fatmi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%